Advancing Access to Justice for Female Victims of Sexual Violence Through Restitution - Indah, Christina Maya; Dwiyatmi, Sri Harini (Unissula, 2024)
Victims of sexual violence often face numerous obstacles in accessing justice, including limited access to restitution mechanisms. Restitution is a form of compensation that victims can receive from perpetrators to recover the losses they have suffered. This paper aims to analyze how access to justice for female victims of sexual violence can be enhanced through restitution mechanisms. The method used is a literature review, examining relevant laws and regulations as well as the practice of implementing restitution in various countries. The analysis reveals that strengthening the implementation of restitution could improve access to justice for victims. This can be achieved by simplifying procedures, providing legal assistance, and enhancing coordination between related institutions, namely law enforcement and the Witness and Victim Protection Agency (LPSK). Additionally, efforts are needed to raise public awareness and increase the sensitivity of law enforcement officers to the issue of sexual violence. By doing so, victims can achieve proper recovery through both institutional and legal mechanisms that support victim protection.